[Freight bill from the Pacific Coast Railway Company to Ah Louis], June 21, 1887 - Pacific Coast Railway Company::::::author::: (1887)
A bill from the Pacific Coast Railway Company to Ah Louis. The charges pertain to the transportation of various goods. The bill amounted to $10.63.